Correlations between basic cannabinoid combinations of plants and non narcotic modern varieties of hemp - Міщенко, С. В. (Scientific Progress & Innovations, 2012)
Established that CBN has minimal relations to other investigated components of cannabinoid of plants variety of Central Russian type USO-14. Due to the strong interconditionality of CBD and THC it is necessary to carry out the selection of plants in which CBD and THC are absent. CBD is the antagonist of basic psychotropic component THC. But his presence is not desirable, because it can be cause of appearance of THC. In south type of Zolotonoshsiy USO-11 CBN is not connected with investigated components of cannabinoid, and correlations and interconnection between three cannabinoid components are weaker comparatively variety of USO-14.